A unified histogram and laplacian based for image sharpening - Pattanasethanon, Petcharat; Attachoo, Boonwat (My University, 2009)
An effective method with enhancement procedures is proposed for image sharpening. Histogram equalization and edge detecting procedures are applied to original images. The mean value, standard deviation, and signal to noise ratio are defined as the statistical index which specifies the brightness, resolution, as well as the sharpness of the image. From the result of output images, the brightness and the contrast of the images were enhanced simultaneously with the sharpness and clearness of the mesh which outweigh the original image appearance. In addition, the advantages of this research indicate a suitable sharpening technique for the image category. ©2009 IEEE.